Ecological gradients of forest vegetation in eastern Fennoscandia - Salemaa, M.; Ilvesniemi, H.; Kryshen, A.; Lukina, N.; Merilä, P.; Oksanen, J. (Hellenic Agricultural Organization "Demeter", 2014)
1